2014
DOI: 10.1186/1755-8166-7-27
|View full text |Cite
|
Sign up to set email alerts
|

Short stature, digit anomalies and dysmorphic facial features are associated with the duplication of miR-17 ~ 92 cluster

Abstract: MicroRNAs (miRNAs) are key regulators of gene expression, playing important roles in development, homeostasis, and disease. Recent experimental evidence indicates that mutation or deregulation of the MIR17HG gene (miR-17 ~ 92 cluster) contributes to the pathogenesis of a variety of human diseases, including cancer and congenital developmental defects. We report on a 9-year-old boy who presented with developmental delay, autism spectrum disorder, short stature, mild macrocephaly, lower facial weakness, hypertel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Two of these studies identified the microduplication of the miR-17-92 cluster on chromosome 13q31.3-containing miR-17, miR18a, miR-19a, miR-19b-1, miR-20a, and miR-92a-1-in patients with autistic traits (64,65). Autistic traits also have been associated with miR-211 deletions and duplications at miRNA Dysregulation in Psychiatry (66).…”
Section: Asdsmentioning
confidence: 94%
“…Two of these studies identified the microduplication of the miR-17-92 cluster on chromosome 13q31.3-containing miR-17, miR18a, miR-19a, miR-19b-1, miR-20a, and miR-92a-1-in patients with autistic traits (64,65). Autistic traits also have been associated with miR-211 deletions and duplications at miRNA Dysregulation in Psychiatry (66).…”
Section: Asdsmentioning
confidence: 94%
“…As an example, miRNAs influence stem cell activity in cardiac, renal, gut, adipose, brain, skeletal, skin and immune tissues by providing a complex feedback system to preserve the stability of gene expression (see below). By contrast, genetic abnormalities in miRNA gene clusters can lead to severe pathologies and may even be (maternally) inherited [11].…”
Section: Mirnas and Developmentmentioning
confidence: 99%
“…Deletion of these genes causes a brachy-syndactyly syndrome (Feingold syndrome type II) [68, 69]. On the other hand, duplication of this gene causes variable skeletal phenotypes; one family shows skeletal overgrowth with polydactyly [70], whereas the other shows short stature and brachydactyly [71]. Mice hemizygous or homozygous for miR17-92 deletion showed reduced skeletal growth with delayed ossification of digital and skull bones [68].…”
Section: The Role Of Mirnas In Osteoblastsmentioning
confidence: 99%